Multilingual wordplays amongst Facebook users in Mongolia - Dovchin, Sender (2016)
© 2016 Walter de Gruyter GmbH, Berlin/Boston. All rights reserved. This study focuses on instances of wordplay in terms of multilingual hybrid forms which are coined by Facebook users in Mongolia. The data show that English and other additional languages such as Russian are creatively and playfully mixed with the Mongolian phonetic, lexical, and syntactic systems. Using multilingual resources, the Facebook users create a new type of multilingual wordplay by which they reference locally relevant meanings and accommodate their own linguistic practices. Such forms of multilingual wordplay indicate the expansion of Mongolian to new linguistic domains, and they have started to extend to offline contexts.